PROGRAM TECHNICAL SYSTEM OF PROVIDING OF SECURITY OF THE INFORMATIVE RESOURCES FOR ON THE CIRCLES OF ELECTRIC POWER SUPPLY - Bakiko, B.M.; Dovgenko, O.O.; Pilinskiy, B.B.; Shvaychenko В.Б. (Journal of Information Technologies in Education (ITE), 2010)
The model of anti-interference protective filter with due account taken of stray parameters of elements is developed. The algorithm of functioning of anti-interference protective filter with integrated system management, which forms the new class of intellectual devices of security of informative resources on the circles of power supply, is offered. The analysis of possibilities of dynamic magnetic biasing of direct current of pericardium of throttle with the use of latitudinal impulsive modulation is experimentally conducted. The efficiency of hardware-software complex of security of informative resources is explored.